Merger as a legal means to restructure troubled insurance companies - Omer, Qaed; Nafea, Khales (Journal of Legal Sciences, 2022)
Economic and commercial developments related to the activities and businesses of companies operating in the insurance sector require dealing with their repercussions and consequences that may affect the existence of those establishments themselves or require their restructuring to adapt to the effects and changes of competition conditions in order to preserve their shares and profits in the market operating in it, and since mergers are among the most important Legal means that constitute solutions to confront the problems and difficulties arising from developments, the laws in general have specified them with provisions regulated by a legal framework that defines the procedures and effects of the correct integration based on legitimate reasons.          As the process of merging insurance companies in order to restructure them has become one of the necessities of the era in which we live now in light of globalization, through a plan to restructure these companies to remove them from their stumble and help them get out of this situation, as insurance companies are now living a new and different reality in light of The increase in their sizes and numbers, and the diversity and multiplicity of the insurance services provided, which requires them to be faster, more flexible and efficient in order to succeed and continue.